A review of Megachile (Chelostomoda) Michener (Megachilidae: Megachilini) known from China with the description of a new species - Niu, Ze-Qing; Wu, Yan-Ru; Zhu, Chao-Dong (Zootaxa, 2012)
The Chinese species of Megachile (Chelostomoda) Michener, 1962, are treated in this paper. Megachile (C.) guangxiensesp. nov. is described and illustrated. A checklist of the known Chinese species, distribution records, and an updated iden-tification key are provided. The type specimens of M. guangxiense are deposited in the Insect Collection of the Institute of Zoology, Chinese Academy of Sciences, Beijing, China (IZCAS, Beijing).